Acupuncture for chronic uncomplicated musculoskeletal pain associated with the spine: A systematic review protocol - Xu, Tao (Medicine (Baltimore), 2019)
BACKGROUND: Chronic uncomplicated neck pain, back pain, and lower back pain, with incidences of 18%, 17.7% and 36%, respectively. Although these three conditions occur in different parts of the body, we can summarize them as chronic uncomplicated musculoskeletal pain associated with the spine (CMPS) in accordance with the pathogenesis. Acupuncture is often used to treat them. We aim to conduct a systematic review to evaluate the efficacy of acupuncture for patients experiencing CMPS. METHODS: The following electronic databases will be searched from inception to Mar 2019: Cochrane Central Register of Controlled Trials, Web of Science, ScienceDirect, PubMed, MEDLINE, EMBASE, Springer, WHO International Clinical Trials Registry Platform, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, VIP Chinese Science and Technology Periodical Database, and Wanfang Database. All randomized controlled trials published in English or Chinese related to acupuncture for CMPS will be included. The primary outcome will be the visual analog scale. Adverse events will be evaluated as secondary outcomes for safety evaluation. Study selection, data extraction, and assessment of study quality will be performed independently by two reviewers. RevMan V.5.3.5 software will be used for the assessment of risk of bias and data synthesis. RESULTS: This study will provide a high-quality synthesis of current evidence of acupuncture for CMPS from visual analog scale. CONCLUSION: The conclusion of our study will provide an evidence to judge whether acupuncture is an effective intervention for patients suffered from CMPS. ETHICS AND DISSEMINATION: Formal ethical approval is not required, as the data are not individualized. The findings of this systematic review will be disseminated in a peer-reviewed publication and/or presented at relevant conferences. PROSPERO REGISTRATION NUMBER: CRD42018114806.